Deforming justice: Representing punishment in The Human Centipede III: Final Sequence. (March 2022) - Kohm, Steven; Walby, Kevin
We analyze the 2015 horror film Human Centipede III: Final Sequence (HC3), written and directed by Dutch filmmaker Tom Six. Engaging with literature on torture porn and body horror, we argue that this film reflects and refracts ideas about crime and punishment including a critical view on mass incarceration in America while critiquing a culture of institutional violence in Western society. By critiquing the institutional violence of the prison in a satirical and visceral manner, we argue Tom Six evades dominant tropes (liberalism, reform, rehabilitation, and escape) prevalent in other prison films and avoids the cinematic tendency to naturalize and reproduce the legitimacy of the prison. We also contend that the film operates at a meta-level to address criticism about the dangers of graphic violence in horror films. HC3 thus offers insight on the disingenuous nature of censorship in a society that condones mass suffering behind bars, systemic racism, and institutionalized punishment of the body for millions.